Efficacy and safety of tirzepatide for treatment of overweight or obesity. A systematic review and meta-analysis - Tan, Bryan (2023)
Background: Recent studies suggest that tirzepatide, a dual glucose-dependent insulinotropic-peptide (GIP) and glucagon-like peptide-1 receptor agonist (GLP-1 RA), has significant weight loss effects. This systematic review and meta-analysis aims to assess the efficacy and safety of tirzepatide for weight loss in patients with overweight or obesity. Methods: Medline, Embase and Cochrane CENTRAL were searched for randomized controlled trials (RCTs) on tirzepatide’s weight loss efficacy for these patients. A single arm meta-analysis of proportions estimated primary outcomes, ≥5%, ≥10%, and ≥15% weight loss, and adverse events (AEs); while meta-analysis of means estimated secondary outcomes. Comparative meta-analysis was conducted between tirzepatide and control arms where mean differences and odds ratios were estimated for continuous and dichotomous outcomes respectively. Results: RCTs included in this study revealed that among 5800 patients, 78.22% (95% CI: 72.15% to 83.73%), 55.60% (95% CI: 46.54% to 64.47%), 32.28% (95% CI: 23.17% to 42.12%) achieved ≥5%, ≥10%, and ≥15% weight loss, respectively. Tirzepatide 5 mg demonstrated weight loss superiority relative to placebo (MD: −12.47 kg, 95% CI: −13.94 kg to −11.00 kg) and semaglutide (n = 1409, MD: −1.90 kg, 95% CI: −2.97 kg to −0.83 kg) with dose-dependent increase for 10 mg and 15 mg doses. The comparison between tirzepatide and semaglutide was examined in the SURPASS-2 trial that was included in this systematic review. For AEs, there was increase odds of experiencing gastrointestinal AEs with tirzepatide compared to placebo, but no significant difference with semaglutide. Conclusion: Tirzepatide has significant potential as a weight loss drug in patients with overweight and obesity, with little increase in AEs compared to other weight loss drugs. With its ability to concurrently target multiple aspects of metabolic syndrome, it should be considered as the next helm of weight loss therapies.